Emergence of linezolid-resistance in vancomycin-resistant Enterococcus faecium ST117 associated with increased linezolid-consumption - Flaminia Olearo; Anna Both; Cristina Belmar Campos; Heike Hilgarth; Eva-Maria Klupp; Jan Lennart Hansen; Florian P. Maurer; Martin Christner; Martin Aepfelbacher; Holger Rohde (Elsevier, 2021)
Objective: We aim to describe the epidemiological, clinical and microbiological characteristics of the linezolid- and vancomycin- resistant Enterococcus faecium (LVRE) in a tertiary care hospital in Germany. Methods: We conducted a retrospective analysis of 196 LVRE cases observed from 1st January 2012 to 31th December 2018. Patients' medical charts were reviewed and available LVRE (n = 102) were subjected to whole-genome-sequencing. Antibiotic consumption was measured in defined daily dose (DDD)/100 bed-days (BD). Results: The prevalence of LVRE isolates among VRE was 6.3 % in 2018. Most patients had an onco-hematological disease (134/196, 68.4 %). From 2012-2018 an increase of +356.7 % of linezolid defined daily dose/100 bed-days was observed. In 71.4 % (90/126, 70 missing values) of the patients, linezolid was prescribed in the previous 6 months. The median exposure to linezolid was 15 days (Interquartile, IQR 9-23). 42/196 (21.4 %) patients had an LVRE-related infection with an overall 30-day mortality rate of 33 %. In 121/196 (61.7 %) patients, linezolid-susceptible VREfm were isolated before LVRE, suggesting secondary acquisition of linezolid resistance. Genetic analysis revealed that most isolates belonged to ST117 (64/102 available isolates, 62.7 %). The G2576T 23S rDNA mutation was identified as the most common resistance mechanism (96/102, 94.1 %). poxtA was identified in two isolates, while cfr, and optrA were not detected. Conclusions: Incidence of LVRE related to 23S rDNA mutations is rising and probably associated with antibiotic consumption. Restrictions in the use of linezolid may be needed in order to retain therapeutic options in VRE.